Message delay for a priority-based automatic meter reading network. - Frigui, Imed
In this paper, we model a data acquisition system as cyclic polling systems with two priority levels. Two types of polling system are studied, exhaustive and time limited service, with application to automatic meter reading. In the case of the exhaustive service strategy, stations are served exhaustively for both priorities, with high priority messages served first on a non-preemptive basis. For the case of the time limited discipline, each station is served for no more than t max but not less than t min. Approximate results are obtained for the high and low priority mean waiting time for polling systems with constant switchover times, N stations, general service times distributions and independent arrival processes for each priority level. Comparisons of the approximations with simulation results for different service distributions, traffic intensities and load combinations show a high degree of accuracy.
Keywords: Polling systems; Mean waiting time; Non-preemptive service discipline; Time limited; Vacation models